Partia Demokratyczna w midterm elections 2010 - Różewicz, Maciej (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2011)
The paper presents the election results of the Democratic Party in the midterm elections 2010. The consequences of these elections encompassed the loss of seats in both houses of Congress as well as the much more painful outcome of the Republican Party winning a majority in the House of Representatives. President Obama assumed complete responsibility for this defeat, and the next two years for him will mean cooperation with the GOP, which will be difficult given the financial crisis. Midterm elections traditionally undermine the party of the President in office – power drains from those who wield it. There always are people who are disappointed with the current policy of the administration, however, in 2010 we can talk about a political earthquake. Apart from the ‘midterm elections effect’, the success of the Republican Party partly resulted from the difficult economic situation and the reform of the health care system. A significant feature of this campaign involved the Tea Party movement, which won a considerable support owing to its critical attitude to President Obama’s domestic policy.
The Democratic Party in the midterm elections 2010